Perception of the user of the psychosocial care center alcohol and other drugs about nursing care (Research, Society and Development, 2020)
We assume that in the state of Piauí, in the city of Teresina, the Psychosocial Care Center on alcohol and other drugs is one of the support devices for chemical addicts, composed by an interdisciplinary team and having as proposals the recovery and rehabilitation of the user who performs the abusive and harmful use of drugs. The nursing professional is part of this team and assumes a very important commitment as a therapeutic agent to provide care and promote support actions to drug users and their families. This research aims to trace the socio-demographic profile of the user, understand the perception of the chemical dependent about the nursing care provided in the psychosocial center and the activities developed in the institution. This was a descriptive exploratory study with a qualitative approach. It had as an instrument of analysis a semi-structured form, applied to fourteen participants who signed the Informed Consent form and the medical records that were used to confirm the information. It obtained three semantic categories in the light of theoretical foundations, the actions/procedures of the nurse to the Capsad client, nursing reception/receptivity versus engagement/permanence of the user in capsad and the donation of nurses in addition to their professional practice, evidencing that the interviewees are satisfied with the nursing care proposed to the service, indicating a good relationship between the team. It is concluded that the nursing professional has its role recognized by the users who favor the service and perform their activities in a humanized way causing benefits to the treatment of addicts.